2019
DOI: 10.1093/ecco-jcc/jjz057
|View full text |Cite
|
Sign up to set email alerts
|

Early Initiation of Anti-TNF is Associated with Favourable Long-term Outcome in Crohn’s Disease: 10-Year-Follow-up Data from the Swiss IBD Cohort Study

Abstract: Background and Aims The optimal timing of treatment escalation in Crohn’s disease [CD] remains a challenging issue, and very little is known about its long-term development following early versus late administration of anti-TNF antibodies. The long-term outcome of Swiss CD patients was comparatively assessed in an up to 10-year follow-up, using patients participating in the Swiss Inflammatory Bowel Disease Cohort Study [SIBDCS]. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Although there is rising evidence that early treatment with anti-TNF agents is superior to early immunomodulators [19][20][21][22], the classic step-up approach still remains standard practice in most European centers. This is in part due to local restrictions that dictate when biologics can be initiated but also due to the lack of validated prognostic markers that can identify at diagnosis which patients will progress and require rescue therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is rising evidence that early treatment with anti-TNF agents is superior to early immunomodulators [19][20][21][22], the classic step-up approach still remains standard practice in most European centers. This is in part due to local restrictions that dictate when biologics can be initiated but also due to the lack of validated prognostic markers that can identify at diagnosis which patients will progress and require rescue therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Common practice in most European pediatric centers is still a step-up approach where biological therapy is generally introduced after failure of corticosteroids, EEN and conventional immunomodulators. However, there is rising evidence that early treatment with anti-TNF is superior to early immunomodulators [16,[19][20][21][22]. Therefore, in the era where new classes of biologics are entering the market, the place of immunomodulators in the treatment of pediatric IBD is questioned.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Swiss IBD Cohort Study (SIBDCS) involving 540 CD patients (the data obtained from patients enrolled in SIBDCS between 2006 and 2012) found that treatment with anti-TNF agents within the first 2 years of CD diagnosis was associated with reduced risk of developing bowel strictures, when compared with initiating these drugs > 2 years after diagnosis (HR, 0.276; p = 0.018) [9]. Recently, the data obtained from SIBDCS involving more patients (246 early initiators and 696 late initiators) over a longer period of time (between 2006 and 2016) also showed that early anti-TNF administration within 2 years of CD diagnosis was associated with reduced risk of osteoporosis and anemia as well as bowel stenosis [10]. Furthermore, patients with early anti-TNF administration sought medical consultations significantly less frequently (including gastroenterologists in private practice, outpatient hospital visits, and a composite of any medical visits) and, by trend, showed lower rates of absence from work owing to CD, in contrast to patients with late anti-TNF administration [10].…”
Section: Discussionmentioning
confidence: 99%
“…Because previous studies have proposed a cut-off time of 2 years for early CD treatment [8][9][10][11], we conducted further analysis to assess the effect of initiation of anti-TNF therapy within 2 years after diagnosis. Of 1,207 patients, 873 started anti-TNF therapy within 2 years of diagnosis, and 334 started anti-TNF therapy > 2 years after diagnosis.…”
Section: Cox Proportional Hazard Regression Analysis For Factors Assomentioning
confidence: 99%
See 1 more Smart Citation